2019
DOI: 10.1007/s00394-019-01988-5
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effect of metabotype on diet–diabetes associations

Abstract: Purpose Inter-individual metabolic differences may be a reason for previously inconsistent results in diet-diabetes associations. We aimed to investigate associations between dietary intake and diabetes for metabolically homogeneous subgroups ('metabotypes') in a large cross-sectional study. Methods We used data of 1517 adults aged 38-87 years from the German population-based KORA FF4 study (2013/2014). Dietary intake was estimated based on the combination of a food frequency questionnaire and multiple 24-h fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 67 publications
(89 reference statements)
1
26
0
Order By: Relevance
“…In previous analyses on metabotyping, [ 8,15 ] we also identified three metabotype clusters in both the KORA F4 and the KORA FF4 studies using extensive sets of grouping variables. We used in total 34 parameters in the KORA F4 study and a subset of 16 parameters in the KORA FF4 study.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In previous analyses on metabotyping, [ 8,15 ] we also identified three metabotype clusters in both the KORA F4 and the KORA FF4 studies using extensive sets of grouping variables. We used in total 34 parameters in the KORA F4 study and a subset of 16 parameters in the KORA FF4 study.…”
Section: Discussionmentioning
confidence: 80%
“…In both metabotyping approaches used in the KORA studies, that is, assignment of participants to existing metabotype clusters identified in NANS (conducted here) and identification of metabotype clusters by cluster analysis, [ 8,15 ] a more metabolically unfavorable cluster 3, an intermediate cluster 2 and a more metabolically favorable cluster 1 were found. However, the two approaches resulted in a difference in the number of individuals per cluster for cluster 1 (34% vs 44%) and cluster 2 (46% vs 36%) with a stable percentage but not the identical individuals in cluster 3 (20% vs 20%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations